Tribological behavior of Fe3C–CNT bilayers grown by plasma-induced metal dusting: Insights into the effect of nanotubes catalyst particles on friction and wear - Thiago De Souza Lamim; Tainá Pigosso; Tainan Daniel Andrioni; Diego Martínez-Martínez; José Daniel Biasoli de Mello; Cristiano Simões Abreu; Aloisio Nelmo Klein; Tatiana Bendo; Cristiano Binder (Friction)
This work investigates the tribological behavior of bilayer surfaces formed by vertically aligned carbon nanotube (VACNT) films grown on top of cementite (Fe3C) layers. Four Fe3C–VACNT surfaces with different morphological and structural aspects were developed using plasma carburizing associated with the metal dusting phenomenon. Their tribological performance was assessed by reciprocating dry sliding tests using a ball-on-flat configuration. The combined analysis of the wear tracks through optical and scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Raman spectroscopy indicates that the catalyst particles of the carbon nanotubes are an essential factor controlling the tribosystem. Lubrication and wear depend on the ratio between the nanotubes and their catalyst particle lengths (LN/LP). VACNT films with LN/LP > 20 promoted friction coefficient (COF) of ~0.08 and reduced the wear rate of the ferrous substrate up to 70%. Wear rates showed an exponential reduction by increasing LN/LP. However, the VACNT film with LN/LP < 10 induced severe abrasive wear since the beginning of the tribotests, leading to worse tribological performance than a reference surface composed of a single Fe3C layer. Furthermore, the initial crystallinity of the VACNT films did not affect the solid lubrication or wear resistance of the surfaces.